59 Diastolic blood pressure, subclinical myocardial damage, and cardiac events: implications for blood pressure control. (28th September 2016) - McEvoy, JW; Chen, Y; Rawlings, A; Hoogeveen, RC; Ballantyne, CM; Blumenthal, RS; Coresh, J; Selvin, E
Abstract : Background: The optimal systolic blood pressure (SBP) treatment goal is in question, with SPRINT (Systolic Blood Pressure Intervention Trial) suggesting benefit for 120 mm Hg. However, achieving an SBP this low may reduce diastolic blood pressure (DBP) to levels that could compromise myocardial perfusion. Objectives: This study sought to examine the association of DBP with prevalent and progressive myocardial damage (using high-sensitivity cardiac Troponin-T, hs-cTnT). We also examined prospective associations between DBP and coronary heart disease (CHD), stroke, or death over 21 years; overall and stratified by subgroups of interest. Methods: We studied 11, 565 adults from the Atherosclerosis Risk in Communities (ARIC) study. We evaluated cross-sectional DBP and hs-cTnT (dichotomized at 14 ng/L) associations with logistic regression, longitudinal associations between DBP and hs-cTnT change using generalised linear models adjusted for attrition, and prospective associations between DBP and events with Cox regression. Results: Mean baseline age was 57 years, 57% of patients were female, and 25% were black. Compared with persons who had DBP between 80 to 89 mm Hg at baseline (ARIC visit 2), the adjusted odds ratio of having hs-cTnT ≥14 ng/l at that visit was 2.2 [95% CI: 1.2–4.1] and 1.5 [1.0–2.3] in those with DBP <60 mm Hg and 60 to 69 mm Hg, respectively. Low DBP at baseline was also independently associated with progressive myocardial damage on the basis of estimated annual change in hs-cTnT over the 6 years between ARIC visits 2 and 4. In addition, compared with a DBP of 80 to 89 mm Hg, a DBP <60mm Hg was associated with incident CHD (HR 1.5 [1.2–1.9]) and mortality (HR 1.3 [1.1–1.6]), but not with stroke. The DBP and incident CHD association was strongest with baseline hs-cTnT ≥14 ng/l (p value for interaction <0.001). Associations of low DBP with prevalent hs-cTnT and incident CHD were most pronounced among patients with baseline SBP ≥120 mm Hg. Conclusions: Particularly among adults with an SBP ≥120 mm Hg, and thus elevated pulse pressure, low DBP was associated with subclinical myocardial damage and CHD events. When titrating treatment to SBP <140 mm Hg, it may be prudent to ensure that DBP levels do not fall below 70 mm Hg, and particularly not below 60 mm Hg.